2021
DOI: 10.18502/jovr.v16i1.8251
|View full text |Cite
|
Sign up to set email alerts
|

An In-Silico Study on the Most Effective Growth Factors in Retinal Regeneration Utilizing Tissue Engineering Concepts

Abstract: Purpose: Considering the significance of retinal disorders and the growing need to employ tissue engineering in this field, in-silico studies can be used to establish a cost-effective method. This in-silico study was performed to find the most effective growth factors contributing to retinal tissue engineering. Methods: In this study, a regeneration gene database was used. All 21 protein-coding genes participating in retinal regeneration were considered as a protein–protein interaction (PPI) network via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…75 A semimechanistic model was developed in rabbits to study ocular PK of various proteins administered IVT; the model was used to estimate half-life in retina, vitreous and aqueous humor in relation to protein size up to a hydrodynamic radius of 14 nm, which is the minimum radius for monomeric AAVs, and the authors suggested that the half-life in each compartment (retina, vitreous, and aqueous humor) could be geometrically scaled to humans. 76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration. 78 Moreover, by coupling network systems biology models with complex QSP models, 75 one could study the drug effects on the downstream disease pathway.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…75 A semimechanistic model was developed in rabbits to study ocular PK of various proteins administered IVT; the model was used to estimate half-life in retina, vitreous and aqueous humor in relation to protein size up to a hydrodynamic radius of 14 nm, which is the minimum radius for monomeric AAVs, and the authors suggested that the half-life in each compartment (retina, vitreous, and aqueous humor) could be geometrically scaled to humans. 76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration. 78 Moreover, by coupling network systems biology models with complex QSP models, 75 one could study the drug effects on the downstream disease pathway.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
“…76 Network systems biology is another promising technique that has been used to study ophthalmic indications for which gene therapy products are being developed; for example, networks of gene regulation have been constructed in glaucoma 9 and AMD, [77][78][79] providing insights into the mechanisms underlying these multifactorial diseases, as well as used to identify the most effective proteins for retinal regeneration. 78 Moreover, by coupling network systems biology models with complex QSP models, 75 one could study the drug effects on the downstream disease pathway.…”
Section: Modeling Efforts For Retina Gene Therapymentioning
confidence: 99%
“…In the current issue of Journal of Ophthalmic and Vision Research, Beheshtizadeh et al report an in-silico study which was aimed to determine the most important growth factors in retinal tissue engineering. [3] Gene ontology (GO) and degree centrality analysis were used to identify the most effective proteins for retinal regeneration. Despite the remarkable results presented in the study, it should be stressed that the growth factors were determined only by degree centrality analysis.…”
mentioning
confidence: 99%